Paths to intervention: What explains the UN's selective response to humanitarian crises? - Martin Binder (Journal of Peace Research, 2015)
Over the past two decades, the United Nations Security Council has responded more strongly to some humanitarian crises than to others. This variation in Security Council action raises the important question of what factors motivate United Nations intervention. This article offers a configurational explanation of selective Security Council intervention that integrates explanatory variables from different theories of third-party intervention. These variables are tested through a comparison of 31 humanitarian crises (1991–2004) using fuzzy-set qualitative comparative analysis. The analysis shows that a large extent of human suffering and substantial previous involvement in a crisis by international institutions are the key explanatory conditions for coercive Security Council action, but only when combined with negative spillover effects to neighboring countries (path 1) or with low capabilities of the target state (path 2). These results are highly consistent and explain 85% of Security Council interventions after the end of the Cold War. The findings suggest that the Council's response to humanitarian crises is not random, but follows specific patterns that are indicated by a limited number of causal paths.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; fuzzy-set analysis; humanitarian crises; humanitarian intervention; United Nations